Novel coronavirus infection SARS-CoV-2 in elderly and senile patients: prevention, diagnosis and treatment. Expert Position Paper of the Russian Association of Gerontology and Geriatrics - O. N. Tkacheva; Yu. V. Kotovskaya; L. A. Aleksanyan; A. S. Milto; A. V. Naumov; I. D. Strazhesko; N. M. Vorobyeva; E. N. Dudinskaya; I. P. Malaya; K. Yu. Krylov; E. A. Tyukhmenev; A. V. Rozanov; et al. (Кардиоваскулярная терапия и профилактика, 2020)
A novel coronavirus infection SARS-CoV-2 (COVID19) is especially dangerous for elderly and senile patients. Preventive measures for elderly people should cover three areas: 1) direct prevention of the viral infection, 2) preservation of the functional status and prevention of geriatric syndromes, including the use of social support measures, 3) control of comorbidities. The clinical pattern of COVID-19 in older patients may be atypical, while the mildness of symptoms (no fever, cough, shortness of breath) may not correspond to the severity of the prognosis. Delirium may be the first manifestation of COVID-19, which requires special care in its screening. Management of elderly and senile patients with COVID19 should include measures for delirium prevention, the detection and improvement of nutrition. The risk of malnutrition with sarcopenia increases with hospitalization of a patient, especially when using artificial ventilation, is associated with an unfavorable prognosis during hospitalization, accelerates the progression of senile asthenia and reduces the quality of life. Geriatric assessment is the cornerstone of determining the management of an elderly patient.